The challenges faced by the catalysts of recyclable materials in Brazil before the prospects of work (Revista LIDER, 2019)
Recyclable material collectors are a segment of workers exposed to all sorts of adversity: working conditions, marginality, unhealthy conditions, insecurity, among others. The role of public policies and management is of fundamental importance to provide necessary support in the perspective of guaranteeing work and income. In this exploratory study, we document the current reality of these workers in Brasil, in the state of Rio de Janeiro, municípality of Duque de Caxias, making visible challenges for policies and public management. The main sources of the research consisted of literature produced by several authors and relevant legislation, electronic media (newspapers, television programs, seminars), and semi-structured interviews. The evidence indicates that the municipality's relationship with workers is of total neglect, lack of local support. Imperative is the existence of public policies that offer workers decent living and working conditions, for example the formalization and inclusion of the recyclable material collectors in the labor market and the participation in the municipal government.